Pemanfaatan Sistem Otomasi Dinas Perpustakaan dan Kearsipan (DISPERSIP) Kota Surakarta Berbasis Senayan Library Management System (SLIMS) - Putra, Adam Purnama; Marintan, Mega Alif (Program Studi Ilmu Perpustakaan dan Informasi, Universitas Islam Nusantara, 2024)
The evolution of the use of information technology in libraries is evidenced by the increasing number of libraries that include information technology as part of their library operations. The term library automation system is well known when information and communication technology is used by libraries. Library automation systems offer libraries a great opportunity to improve services in the library. The use of information technology is very significant for libraries because it aims to provide the best service and meet the increasingly complex information needs of library users. The purpose of this research is to understand the use of library automation features in the Senayan Library System